Omalizumab for management of refractory urticaria: Experience of a tertiary care centre in Eastern India - Shekhar Neema; Manas Chatterjee (Indian Journal of Dermatology, 2018)
Aim: To study the effects of omalizumab in chronic spontaneous urticaria in Indian patients. Setting and Design: The study was conducted in a tertiary care centre and it was retrospective and descriptive in nature. Material and Methods: We analysed the data of patients who were administered omalizumab between June 2014 and June 2015 for the management of refractory chronic spontaneous urticaria at our centre. Omalizumab was used in those patients who did not respond to updosing of antihistaminics and cyclosporine. Omalizumab was used in dose of 300 mg per month for 3 doses. Results: Twenty-four patients were administered omalizumab during the study period. Average age of the patients was 36.54 years, female:male ratio was 1.4:1, mean duration of disease was 20.66 months, and autologous serum skin test was positive in 33% of studied individuals. Ninety six percent of cases showed response to treatment in our study. Remission was seen in 25% of patients, 50% showed satisfactory response, and 20.83% showed partial response. Average UAS7 scoring before starting omalizumab in preceding week was 24.4. Average UAS7, 2 weeks after starting omalizumab was 4 in responsive patients. Conclusion: Omalizumab is safe and effective treatment for the management of chronic spontaneous urticaria. It can be used in Indian setting after failure to other third-line therapies such as addition of montelukast and cyclosporine due to high cost of treatment.